REKONSTRUKSI MANAJEMEN DAKWAH QURAISH SHIHAB: PENDEKATAN HUMANIS DALAM TAFSIR AL-QUR’AN - Lailatul Lutfiyah; Nurin Nafilah Putri; Nanik Handayani; Siti Hanum; Anang Sholikhudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Which reduces their effectiveness in modern plural societies. The objective of this study is to analyze the principles of da'wah management within Quraish Shihab’s interpretative framework and to formulate a humanistic reconstruction model that is more adaptive and inclusive. This research employs a qualitative method using a library research approach, with data collected from primary sources such as Tafsir Al-Mishbah and supported by relevant scholarly literature. The data are analyzed using content analysis to identify key themes related to humanism and da'wah management. The findings indicate that Quraish Shihab’s approach emphasizes contextual understanding, ethical communication, tolerance, and empathy as central elements in delivering Islamic messages. The reconstructed model of da'wah management highlights strategic planning based on social context, persuasive and dialogical communication, inclusive implementation, and evaluation focused on social impact rather than mere numerical outcomes. This approach contributes to developing a more relevant, moderate, and human-centered model of Islamic preaching in contemporary society.